The Effect of the Role-Playing Method on the Mental Health of Group B Children at Brang Ene 2 State Kindergarten, West Sumbawa - Amrina Roshada; Baik Nilawati Astini; Ika Rachmayani; Gunawan Gunawan (Indonesian Journal of Elementary and Childhood Education, 2026)
Early childhood mental health frequently receives insufficient attention in school-based learning activities, despite its fundamental role in children's socio-emotional development. One intervention that can be implemented to support mental health is the role-playing method. This study aims to analyze the impact of the role-playing method on the mental health of Group B children at Brang Ene 2 State Kindergarten, West Sumbawa Regency. A quantitative approach with a pre-experimental one-group pretest-posttest design was employed. Data were collected using structured observation sheets. The research sample consisted of 15 children in Group B. Data analysis was performed using the Paired Samples T-test via SPSS 30.0 for Windows. The results indicated a significant difference between pretest and posttest scores, where the average score increased from 50.27 to 69.87. Hypothesis testing yielded a significance value (2-tailed) of 0.001 (p < 0.05), demonstrating that the role-playing method has a significant effect on children's mental health. Consequently, role-playing serves as an effective alternative instructional strategy to foster mental health development in early childhood education settings.